E-Government Development & Digital Economy: Relationship - Uddin, Mohammad Gias; Uddin, Mohin (American Economic & Social Review, 2020)
The main objective of this examine is to explore the elements that influencing the digital economic system and E-government courting. Commonly, the examiner is to analyze the impact of demographic variables are gender and schooling stage; as well as digital infrastructure, virtual readiness, virtual content material, and offerings on the digital economy in Malaysia. A minimum overall of 384 questionnaires could be disbursed to the goal respondents to collect the sample information. Four hypotheses helping to the developed to survey the particular targets of the examiner. Demographic variables expected to have a high-quality enormous relationship with the virtual financial system. Last however now not least, the findings of the look at shall offer statistics to E-government to understand what factors will affect the virtual economic system. Except, it shall additionally provide useful information for E-government to higher fit their people’s needs. The elements decided to boom high-quality dating among E-government and virtual financial system in Malaysia.